2018
DOI: 10.1016/j.jaccedu.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Accounting education literature review (2017)

Abstract: This review of the accounting education literature includes 103 articles published during 2017 in six journals: (1) Journal of Accounting Education, (2) Accounting Education, (3) Advances in Accounting Education: Teaching and Curriculum Innovations, (4) Global Perspectives on Accounting Education, (5) Issues in Accounting Education, and (6) The Accounting Educators' Journal. We update 12 prior accounting education literature reviews by organizing and summarizing contributions to the accounting education litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 81 publications
0
20
0
11
Order By: Relevance
“…Firstly, regardless of the systematic procedure of literature review (Supriya et al, 2018), theories and previous studies, sources of literature review, primarily predict Indonesian EFL undergraduate's lexical density. It was caused by the fact that the literature synthesis helps the writers develop a knowledge base (Apostolou, Dorminey, Hassell, & Rebele, 2018) in writing the undergraduate thesis. Secondly, the position of the introduction section at the beginning of the scientific report, presumably reviewed more frequently and intensively, does not affect lexical density.…”
Section: Results and Discussion Lexical Densitymentioning
confidence: 99%
“…Firstly, regardless of the systematic procedure of literature review (Supriya et al, 2018), theories and previous studies, sources of literature review, primarily predict Indonesian EFL undergraduate's lexical density. It was caused by the fact that the literature synthesis helps the writers develop a knowledge base (Apostolou, Dorminey, Hassell, & Rebele, 2018) in writing the undergraduate thesis. Secondly, the position of the introduction section at the beginning of the scientific report, presumably reviewed more frequently and intensively, does not affect lexical density.…”
Section: Results and Discussion Lexical Densitymentioning
confidence: 99%
“…With respect to accounting historians, it is "not yet the subject of significant study" (Edwards, 2011a: 37). It is even less evident in the accounting education literature: a series of reviews of publications in the leading accounting education journals (Apostolou et al, 2010(Apostolou et al, , 2013(Apostolou et al, , 2015(Apostolou et al, , 2017 found that among the numerous themes appearing in those publications, a historical perspective on accounting education is marginal, not present in all the journals, and it is almost non-existent if the focus is on the period before the 19 th century. Our knowledge of how accounting education, and thus, accounting practice evolved is therefore "far from comprehensive" (Evans & Paisey, 2018: 3).…”
Section: The History Of Accounting Educationmentioning
confidence: 99%
“…Some of the previous studies have explored links between aspects of teaching, the learning context or instructional interventions and student performance. However, the relationships between student self-reporting on their learning experiences and actual performance outcomes were not examined (Apostolou, Dorminey, Hassell, & Watson, 2013), particularly considering student demographic characteristics, such as gender, previous level of education, experience of online studies or study in a specific disciplinary area. Furthermore, most of the previous research was either conducted in the context of traditional classrooms, where online tests are used in addition to face-to-face delivery or in a blended mode, where students have regular face-to-face contact with their instructor and with other students in addition to online interaction.…”
Section: Gaps In Knowledge and Research Questionsmentioning
confidence: 99%